Design parameter evaluation based on human operation for tip mechanism of forceps manipulator using surgical robot simulation. (2nd April 2016) - Kawamura, Kazuya; Seno, Hiroto; Kobayashi, Yo; Ieiri, Satoshi; Hashizume, Makoto; Fujie, Masakatsu G.
Abstract: We proposed a design method for pediatric surgical robots that evaluates the workspace and view information in computer simulator before the actual robot is developed. In this study, we investigated a suturing task in a virtual environment using forceps manipulators with different mechanical parameters. We reproduced the surgical workspace for congenital esophageal atresia and measured the working volume and invisible area to obtain suitable parameters for the suturing task. We also calculated the suitable mechanical parameters using Pareto optimal solution method and verified the mechanical parameters in Pareto optimal solution. We verified from the experimental results that there is a trade-off between the working volume and invisible area during the suturing task. Moreover, we determined from the calculation results that the mechanical design of the forceps manipulator is influenced by the invisible area during the suturing task. Finally, we confirmed that it is possible to obtain suitable parameters for surgical robots using the proposed method. Abstract :